From Table to Trash: Behavioral Insights into Food Waste in Klang Valley Restaurants - Suraya Azmi; Siti Nur Aisyah Abdullah; Noorazlin Ramli; Yusnaidi (Information Management and Business Review, 2025)
Food waste has significant environmental impacts and poses a major challenge for restaurant operations in the Klang Valley. To examine the elements of the Norm Activation Model (NAM) that influence consumer intentions to reduce food waste, a quantitative method was utilized to select 290 respondents. 290 valid responses were collected through face-to-face data distributions and an online questionnaire before being analyzed using the Statistical Package for the Social Sciences (SPSS). The study examines how personal norms (PN), ascription of responsibility (AR), and awareness of consequences (AC) influence personal norms (PN) and how personal norm (PN) influences intention (INT) to reduce food waste. Findings reveal that the intention to reduce food waste (INT) is significantly influenced by personal norms (PN), with awareness of consequences (AC) and ascription of responsibility (AR) both positively influencing personal norms (PN). These interventions align with the NAM model by increasing awareness, reinforcing responsibility, and shaping personal norms that encourage sustainable dining behaviors among consumers. Thus, the findings of the study benefit all key stakeholders, including restaurants, policymakers, and consumers, by advocating effective solutions to minimize food waste in the Klang Valley’s restaurants.